Numerical homogenization of multi-scale heterogeneous media - M. I. Epov; E. P. Shurina; M. K. Artemyev (Геофизический журнал, 2012)
A problem of electrical potential distribution in media, containing micro-inclusions with highly contrasting physical properties and different geometric shapes, was considered. Multiscale finite element method has been chosen as a solver. A procedure of homogenization of electrical resistivity of heterogeneous media was held, using the solution of original task. The results of numerical modeling were compared with the results of physical experiment.